Dinâmicas territoriais em Distancia de rescate, de Samanta Schweblin: considerações sobre o território latino-americano - Cruz, Lucas Sauzem (2023)
In order to observe territorial forms that cross Latin America, this work has as its main object of analysis the territorial dynamics developed in the fictional universe of the narrative Distancia de rescate (2014), by the Argentine writer Samanta Schweblin. However, to give horizontality to the Latin American territorial perception, two brief literary analyses are included embracing De gados e homens (2013), by the Brazilian writer Ana Paula Maia, and Temporada de huracanes (2017), by the Mexican writer Fernanda Melchor. In the composition of master thesis, the theoretical foundation on the concepts of territory and deterritorialization is conducted from studies by the geographer Rogério Haesbaert, in particular his book O mito da desterritorialização: do “fim dos territórios” à multiterritorialidade (2011). In the aftermath, we seek to understand what is comprehended as Latin America, having as a critical basis essays by Walter Mignolo (2005), and Darcy Ribeiro (1986), and the context of current literary production, where the analysed narratives are situated, especially from the considerations by Josefina Ludmer (2013), Florencia Garramuño (2014), and Alberto Giordano (2010). For the analysis of Distancia de rescate, studies by Leone (2016, 2017) on Argentinean rural imaginary are essential supports, since the book presents a problem that involves the relationship between human being and natural environment of the pampa gaúcho, in which Capitalist market actions are evidenced that violate the countryside ecosystem and transform the ways of being in this territory into corruption. Thus, in the end, the outline of a hostile zone for human life is perceived, which causes the erasure of the identification of some subjects with the territory and deforms those who persist in living there. As for Latin American territorialities, the three novels trace territories that suffer from the absence of State power, the presence of capitalist enterprises in rural regions, forms of violence in private and public daily life, forces that corrupt the humanity of the subjects and with the melancholy of a prediction of a perverse and increasingly excluding future.